Návrh na snížení nezaměstnanosti v okrese Vyškov - Cabalka, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato diplomová práce se týká problematiky nezaměstnanosti v okrese Vyškov v letech 2007 – 2011. Práce obsahuje analýzu všech skupin nezaměstnaných v korelaci k věku, dosaženého vzdělání, pohlaví, stavu zdraví a délce nezaměstnanosti. Dále se v práci nachází několik návrhů řešení, které by měly prolomit značně neuspokojivý stav míry nezaměstnanosti ve zmíněném okrese.

This diploma work deals with problem of unemployment in the district of Vyškov in the years 2007-2012. This work includes analysis of all unemloyment groups in relation to age, education, sex, state of health and unemloyment lenght. Furthermore the diploma works with several proposed solutions that could break largely unsatisfactory state of the unemloyment rate in the mentioned district.
Suggestion for Reduction of Unemployment in the District of Vyškov
Keywords: Práce; trh práce; nezaměstnanost; aktivní politika zaměstnanosti; pasivní politika zaměstnanosti; Labour; labour market; unemployment rate; active employment policy; passive employment policy